The shrinking middle: exploring the nexus between information and communication technology, growth, and inequality - Yeo, Yeongjun; Hwang, Won-Sik; Lee, Jeong-Dong (Technological and Economic Development of Economy, 2023)
To implement specific actions to respond to challenges accompanied by technological advances, it is essential to realize the foreseen future at different levels. This study aims to generate the forecasts of different prospects of different industries, labor market, and households, depending on the pervasiveness of the information and communication (ICT) software (SW) in production. For the analysis, we propose a computable general equilibrium (CGE) model that explicitly incorporates diverse impact channels induced by ICT SW investments. Our simulation results suggest that the development of ICT SW technology can bring about both opportunities and challenges in the economic system. The results also show that advancements in ICT SW can aggravate inequalities within the economic system, while driving higher economic growth effects by accelerating the polarization of the labor market and wages/income distributions. Accordingly, our results suggest that policymakers should formulate tailored policy options to mitigate structural problems and widen income disparities driven by ICT-specific technological advances to achieve economic inclusiveness.